BONEKA DENGAN ESTETIKA KHAS PENARI GAMBYONG - Yulia, Rizqa Sari; Soedarwanto, Hady (Anggada : Jurnal Desain dan Seni, 2021)
Currently, toys are a medium that is also favored by adults. One type of toy that is popular and widely collected by adults is a doll. Collectible dolls are usually too fragile, complicated, or expensive for children’s toys. In doll products today, there is a design trend that is inspired by traditional culture. This could be due to cultural preservation and nostalgia for the owner. Regarding cultural preservation, Indonesia itself has many unique cultures in each region such as the Gambyong dance. The tenderness and beauty of the female figure that is reflected in the Gambyong dance is in line with the essence of dolls in general. Because of these things, an idea emerged to design a doll with the theme of a Gambyong dancer that adults could collect.